2017
DOI: 10.1556/066.2017.46.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of aroma-active compounds in commercial aged rums

Abstract: The volatile compounds in commercial rums declared as aged 3, 7, 10, and 15 years were isolated by solvent extraction followed by solvent-assisted fl avour evaporation and analysed by gas chromatography-olfactometry. According to the aroma extract dilution analysis, 19 potentially aroma-active compounds in the fl avour dilution (FD) factor range of 8 to 1024 were found. Fifteen of them were present in at least one aged rum at FD factor≥128. Clear differences in the FD factors of these odourants between each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…A sensory wheel is an essential tool for understanding the complex and distinct flavour profile of cachaça, and it was created using carefully selected terms (Figure 10) [10,14,38,42,48,78,80,94,115,116,131,138,152,156,157,159] (see Appendix D). The sensory wheel is divided into three tiers, with the first tier categorizing the overall flavour profile into broader terms.…”
Section: Analysing the Aroma Profile Of Cachaça: Implications For Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…A sensory wheel is an essential tool for understanding the complex and distinct flavour profile of cachaça, and it was created using carefully selected terms (Figure 10) [10,14,38,42,48,78,80,94,115,116,131,138,152,156,157,159] (see Appendix D). The sensory wheel is divided into three tiers, with the first tier categorizing the overall flavour profile into broader terms.…”
Section: Analysing the Aroma Profile Of Cachaça: Implications For Pro...mentioning
confidence: 99%
“…Research has shown that yeast strains significantly impact the creation of the distinctive aroma compounds in cachaça, and the type of distillation device used influences the chemical profile of the samples. Moreover, cachaça and rum have different aroma profiles, with specific odorants being more potent in cachaça than in rum [9,10,89,[159][160][161]. Sensory evaluations have demonstrated that cachaças produced in copper stills and aged in oak casks are preferred, and the intensity of yellow colour, wood flavour, sweetness, and fruit aroma positively correlate with preference.…”
Section: Analysing the Aroma Profile Of Cachaça: Implications For Pro...mentioning
confidence: 99%